A Subroutine Package for Solving Hydrodynamic Lubrication Problems - Basri, Shah Nor (1991)
The paper presents a subroutine package that solves the problem of hydrodynamic lubrication operating under isothermal film. The underlying analysis and computational algorithm are described. The finite element method was used for solving the pressure equation for cases of both laminarand turbulentflow. A representative example of a three-lobeprofile bore bearing is used to demonstrate the application of the subroutine package..